Floristic composition, diversity and community structure in a secondary rainforest in Ibadan, Nigeria (2021)
Secondary forests may act as buffer area and serve as reservoir for biotic components that are lost from primary forest due to anthropogenic disturbances. This study investigated the floristic composition, diversity and community structure of Cocoa Research Institute of Nigeria (CRIN), Idi-Ayunre, Ibadan, Nigeria. Twenty-five main plots (each 50 m × 50 m) were randomly mapped out to enumerate tree species, five 10 m × 10 m sub-plots were systematically mapped out within each main plot to enumerate shrubs and three quadrats (1 m × 1 m) were laid in each sub-plot to enumerate herbaceous species in Wet Season (WS) and Dry Season (DS). Relative Importance Value (RIV), Taxa, Individuals, Dominance, Shannon-Wiener, Equitability and Jaccard similarity index were determined. A total of 181 plant species from 145 genera and 54 families which included 63 trees, 33 shrubs and 85 herbaceous species were enumerated. In wet season, Triplochiton scleroxylon, Lonchocarpus griffonianus and Chromolaena odorata had the highest RIV while in dry season, Terminalia superba, Lonchocarpus cyanescens and C. odorata were the highest for trees, shrubs and herbs, respectively. Low dominance but high equitability and Shannon-Weiner values indicated inter-specificity among trees, shrubs and herbs. It was only in herbs that Jaccard-similarity was less than 100% across seasons. Resilience for keystone species conservation is possible due to flora species heterogeneity of the study site.